Control of IFN-γ production and regulatory function by the inducible nuclear protein IκB-ζ in T cells. Issue 3 (27th May 2015) - MaruYama, Takashi; Kobayashi, Shuhei; Ogasawara, Kouetsu; Yoshimura, Akihiko; Chen, WanJun; Muta, Tatsushi
Abstract : Nuclear IκB-ζ, a target of TGF-β signaling in T cells, controls immune homeostasis and IFN-γ production. Abstract: The transcriptional regulator IκB-ζ is important for the control of apoptosis in keratinocytes. Thus, IκB-ζ-deficient mice develop autoimmune diseases, such as Sjögren's syndrome. However, T cells also play a pivotal role in Sjögren's syndrome. To study the role of IκB-ζ in T cells, we generated T cell-specific, IκB-ζ-deficient mice. We observed increased numbers of peripheral effector/memory CD4 + cells and IFN-γ-producing CD4 + cells in 3-week-old mice. We found that IκB-ζ can be up-regulated by TGF-β1 in naϊve CD4 + T cells and that it negatively regulates IFN-γ expression. In addition, we generated Treg -specific, IκB-ζ deficient mice and found that IκB-ζ is dispensable for the plasticity and stability of Tregs . However, Tregs from T cell-specific, IκB-ζ-deficient mice have reduced immunoregulatory function. Thus, our data reveal a previously unappreciated role for IκB-ζ in IFN-γ production in T cells and the immunoregulatory function of Tregs .